Unlocking the Potency of Endophytic Fungi: Connecting Discovery Endophytic Fungi for Bioactive Compound - Shivakumar, Sagar Mysore; Gopalakrishna, Rashmi Nelligare (International Journal of Pharmaceutical Investigation, 2025)
Endophytic fungi have engrossed the most attention owing to their prospect of being a source of many bioactive compounds. These fungi are regarded as effective producers of valuable metabolites, such as antibacterial, antifungal, anticancer and antiviral substances, which are crucial in the fight against the growing global healthcare problem of antimicrobial resistance. Also, new DNA sequencing technologies, metagenomics, and LCMS require searching for new fungi and their bioactive substances though isolation is still useful. Additionally, these compounds can also be produced using co-cultivation or genetic manipulation techniques. Reports stress the fact that endophytic fungi possess the ability to produce a considerable array of unique compounds from terpenes to alkaloids to peptides, with applications as anti-microbials, anticancer, and anti-inflammatory agents. The work done here emphasizes the importance of endophytic fungi in the development of green and eco-friendly medicines for the treatment of chronic diseases and infections.
Keywords: Anticancer; Anti-Inflammatory; Antimicrobial Properties; Bioactive compounds; Endophytic Fungi